The Glagolitic Script in Medieval Europe Literature - Večerka, Radoslav (Bohemica Olomucensia, 2015)
The study discusses the origin of the Glagolitic script using Medieval Slavic texts as material for the reconstruction. Territorially, the old Glagolitic script was first used in The Byzantine Empire, than in Great Moravia (and for a short time in Pannonia), in The Duchy of Bohemia, temporarily in Hungaria and after that in The Kingdom of Bohemia; peripherally alos in Russia and in particular, quite frequently, in White Croatia (especially after the Pope approved its use by the Catholic Church). Afterwards the Glagolitic script was used from the 15th century on in the Abby of Saint-Remi in France. As far as the language is concerned, the script was used in the Proto-Old Church Slavonic, Great Moravian, classic (canonized) Old Church Slavonic texts as well as in the later Church Slavonic Czech, Russian and White Croatian redactions, and, what is more, even in the Old Czech texts (in biblical and some catechetical texts' translations from Latin).
Keywords: Glagolitic script; Old Church Slavonic; Medieval Slavic manuscripts